Eutypellazines A–M, thiodiketopiperazine-type alkaloids from deep sea derived fungus Eutypella sp. MCCC 3A00281. Issue 53 (3rd July 2017) - Niu, Siwen; Liu, Dong; Shao, Zongze; Proksch, Peter; Lin, Wenhan
Abstract : Bioassay and NMR/MS guided fractionation resulted in the isolation of 13 new alkaloids from marine fungus Eutypella sp. Abstract : Bioassay in association with the NMR/MS spectroscopic data guided fractionation of the solid fermentation of a deep sea derived fungus Eutypella sp. MCCC 3A00281, resulted in the isolation of 13 new thiodiketopiperazine-type alkaloids, namely eutypellazines A–M (1–13 ). Their structures were elucidated on the basis of extensive spectroscopic data analysis, including the ECD data, modified Mosher's method, and the Cu-Kα X-ray single-crystal diffraction experiments for the determination of the absolute configurations. An anti-HIV bioassay indicated that compounds1–12 exhibited inhibitory effects against pNL4.3.Env-.Luc co-transfected 293T cells (HIV-1 model cells) with low cytotoxicity, of which eutypellazine E exerted the highest activity. A preliminary structure–activity relationship was discussed. In addition, eutypellazine J (10 ) and epicoccin A showed reactivating effects toward latent HIV-1 in J-Lat A2 cells.